Antimicrobial and FAD synthetases modulating activities of leporins A-C isolated from the sponge-associated fungus Trichoderma sp. - FITJE LOSUNG; ELVY L. GINTING; BOBBY ABDJUL; MAGIE M. KAPOJOS; WILMAR MAARISIT; FENY MENTANG; DEISKE A. SUMILAT; WALTER BALANSA; REMY E. P. MANGINDAAN (Society for Indonesian Biodiversity, 2023)
Abstract. Losung F, Ginting EL, Abdjul B, Kapojos MM, Maarisit W, Mentang F, Sumilat DA, Balansa W, Mangindaan REP. 2023. Antimicrobial and FAD synthetases modulating activities of leporins A-C isolated from the sponge-associated fungus Trichoderma sp. Biodiversitas 24: 6502-6515. The emergence of microbial resistance poses a formidable threat to human health, requiring the discovery of new antibiotics. In this study, we investigated the antimicrobial potential and molecular structures of the metabolites produced by a sponge's symbiont fungal species, Trichoderma sp., in vitro against S. aureus IAM 12544T and Candida albicans IFM 4954 and in-silico against the emerging antibacterial target, prokaryotic bifunctional synthetases (FADS). The molecular structures were determined using spectroscopic techniques (1D, 2D NMR, HRESIMS), while the assessment of biological activities, physicochemical properties, and molecular modifications was performed through a slightly modified disk agar diffusion method, molecular docking, SwissAdme and pkCMS tools, and bioisosterism, respectively. The analysis of spectroscopic data supported the identification of leporins A-C (1-3) as the metabolites, which exhibited strong binding affinities against the 2X0K protein target (-8.9 to -9.4 kcal/mol). Despite their being slightly weaker than known FADS modulators such as compounds 4 (-10.5 kcal/mol) and 5 (-10.5 kcal/mol), leporins A-C demonstrated a stronger binding affinity than compound 6 (-9.6 to -10.5 kcal/mol). Notably, substituting a methyl group with a fluorine atom in 1-3 resulted in lepofluorins A-C (1a-3a), which exhibited enhanced binding affinities and improved physicochemical properties compared to the existing FADS modulators. These findings suggest that leporins A-C (1-3), particularly lepofluorins A-C (1a-3a), have potential as putative novel modulators of FADS. This study provides valuable insights into the design and development of new antibiotics to combat microbial resistance.